2015
DOI: 10.7494/opmath.2015.35.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Levinson's inequality and exponential convexity

Abstract: Abstract. We give a probabilistic version of Levinson's inequality under Mercer's assumption of equal variances for the family of 3-convex functions at a point. We also show that this is the largest family of continuous functions for which the inequality holds. New families of exponentially convex functions and related results are derived from the obtained inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In [8], Adeel et al generalized Levinson's inequality for 3-convex function by using two Green functions. In [9], Pečarić et al gave a probabilistic version of Levinson's inequality (2) under Mercer's assumption of equal variances (but for a different number of data points) for the family of 3-convex functions at a point. They showed that this is the largest family of continuous functions for which inequality (2) holds.…”
Section: Theorem 5 Let F Be a 3-convex Function Onmentioning
confidence: 99%
“…In [8], Adeel et al generalized Levinson's inequality for 3-convex function by using two Green functions. In [9], Pečarić et al gave a probabilistic version of Levinson's inequality (2) under Mercer's assumption of equal variances (but for a different number of data points) for the family of 3-convex functions at a point. They showed that this is the largest family of continuous functions for which inequality (2) holds.…”
Section: Theorem 5 Let F Be a 3-convex Function Onmentioning
confidence: 99%
“…In fact, it corresponds to a probabilistic version of the Levinson inequality derived in [10] (see Theorem 2.3). The proof in our setting is given for the reader's convenience.…”
Section: A( P)mentioning
confidence: 99%
“…Motivated by Witkowski's ideas, Pečarić et al [10] (see also [1]), showed that under Mercer's assumption (1.4) the Levinson inequality holds for a more general class of functions described in the following definition. Definition 1.1 Let : I → R and c ∈ I 0 , where I 0 is the interior of the interval I .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations